Changes in drug transport and metabolism and their clinical implications in non-alcoholic fatty liver disease. (3rd June 2017) - Dietrich, Christoph G.; Rau, Monika; Jahn, Daniel; Geier, Andreas
ABSTRACT: Introduction : The incidence of non-alcoholic fatty liver disease (NAFLD) is rising, especially in Western countries. Drug treatment in patients with NAFLD is common since it is linked to other conditions like diabetes, obesity, and cardiovascular disease. Consequently, changes in drug metabolism may have serious clinical implications. Areas covered : A literature search for studies in animal models or patients with obesity, fatty liver, non-alcoholic steatohepatitis (NASH) or NASH cirrhosis published before November 2016 was performed. After discussing epidemiology and animal models for NAFLD, we summarized both basic as well as clinical studies investigating changes in drug transport and metabolism in NAFLD. Important drug groups were assessed separately with emphasis on clinical implications for drug treatment in patients with NAFLD. Expert opinion : Given the frequency of NAFLD even today, a high degree of drug treatment in NAFLD patients appears safe and well-tolerated despite considerable changes in hepatic uptake, distribution, metabolism and transport of drugs in these patients. NASH causes changes in biliary excretion, systemic concentrations, and renal handling of drugs leading to alterations in drug efficacy or toxicity under specific circumstances. Future clinical drug studies should focus on this special patient population in order to avoid serious adverse events in NAFLD patients.